Value Orientation and Personality Dimensions of Students Pursuing Diverse Academic Disciplines - Lovleen (My University, 2018)
Personal values and personality dimensions have been a main subject of concern for researchers since long. Theoretical and empirical research provides the evidence regarding influence of personal values and personality dimensions in the decision regarding career. The major objective of the present study was to compare personal values, personality dimensions, and self-esteem of male and female students studying in Arts/Humanities (A/H) and Business/Technical (B/T) academic fields. The study was conducted in India, with the sample of 1200 students in the age range 18-25 years (for total sample, M = 21.5, SD = 2.9; for males, M = 21.1, SD = 2.7; for females, M = 20.5, SD = 2.1), drawn from various educational institutions of Punjab. The sample included 600 students from A/H field (300 males and 300 females) and 600 students from B/T field (300 males and 300 females). Intrinsic and extrinsic personal values were measured by Aspiration Index (AI) which yielded two dimensions of scores: Importance and Likelihood. Importance of values indicated the amount of priority they place on a specific value, while likelihood of values indicated the expectancy of occurrence of those values and goals in their future. Personality traits of extraversion, neuroticism, and psychoticism were measured by using Eysenck Personality Questionnaire- Revised (EPQ-R). Self-esteem was measured by using Rosenberg Self-Esteem Scale (RSES). The present research employed personal values: importance, personal values: likelihood, psychoticism, neuroticism, extraversion, and self-esteem as independent variables (predictors) and choice of academic discipline as dependent (criterion) variable. Mean, Standard Deviation (SD), and t-test were used to compare the scores of students on personal values, subscales of personal values, and personality dimensions for the two academic fields and to analyse gender differences. Binary logistic regression was carried out to identify the best predictor among personal values and personality dimensions of the choice of academic discipline in males and females. The results revealed that A/H students had more inclination towards intrinsic values such as self-acceptance, community feeling and affiliation, while B/T students were more oriented towards extrinsic values such as financial success, attractive appearance, and social recognition. Similar pattern of results emerged for the Importance and Likelihood of values. A/H students scored highest on the value of on subscale- affiliation (importance) and B/T students scored highest on subscale-financial success (importance) value A/H students were found to be high on extraversion, low on psychoticism and neuroticism and vice versa for B/T students. A/H students had higher self-esteem in comparison to B/T students. The results also indicated gender differences. Females had more intrinsic value orientation whereas males had more extrinsic value orientation. Overall, females had highest score on value subscale-affiliation (importance), while males had highest score on subscale- financial success (importance) value. Females also scored high on extraversion and low on neuroticism and psychoticism as compared to males. Females had higher self-esteem than males. Among the personal values studied, Extrinsic values: Importance emerged as the best predictor of B/T academic choice and Psychoticism emerged as the best predictor among personality dimensions for B/T academic discipline. And among all the variables studied, Extrinsic values: Importance (subscale-financial success) came out to be the best predictor of B/T academic discipline. Extrinsic values: Importance and Extrinsic values: Likelihood emerged as the best predictors of B/T academic field in males and females respectively. Findings are explained in terms of self-determination theory and changing academic choices leading to possible shift in value orientation and personality dimensions of Indian youth. The present study advances previous findings on two counts: (i) The present study involved students belonging to completely different educational domains and (ii) The study compared the students from the different domains on grounds of value orientation, personality dimensions and self-esteem to explore the effect these variables on students’ career related decisions.
Keywords: Value Orientation; Personality Dimensions; Self Esteem; Academic Disciplines; Self Determination Theory